Emotional Mimicry in Social Context: The Case of Disgust and Pride - Fischer, Agneta; Becker, Daniela; Veenstra, Lotte (Frontiers in Psychology, 2012)
A recent review on facial mimicry concludes that emotional mimicry is less ubiquitous than has been suggested, and only occurs in interactions that are potentially affiliative (see Hess and Fischer, in revision). We hypothesize that individuals do not mimic facial expressions that can be perceived as offensive, such as disgust, and mimic positive emotion displays, but only when the context is affiliative (i.e., with intimates). Second, we expect that in spontaneous interactions not mimicry, but empathic feelings with the other predict the accurateness of emotion recognition. Data were collected in a pseudo-experimental setting, during an event organized for subscribers of a large Dutch women’s magazine. One woman (expresser) was exposed to two emotional stimuli (i.e., a vile smell, a compliment) in order to evoke disgust and pride respectively. Another woman (observer: intimate or stranger) was sitting opposite of her. We collected self-report measures on emotions and empathy, and coded facial expressions of disgust and smiling on the basis of FACS. The results show that participants do not mimic disgust. In contrast, smiles displayed after the vile smell and the compliment were mimicked, but only among intimates. We also found that self-reported empathy and not mimicry is related to the recognition of disgust. These findings are discussed in the light of a Social Contextual view on emotional mimicry.